Transformation of English Speaking Skills in Indonesian Phenomenology: Transformasi Keterampilan Berbicara Bahasa Inggris dalam Fenomenologi Indonesia - Ramadhan, Adinda Shafira; Taufiq, Wahyu (Inquest Journal, 2025)
This study investigates the implementation of the English Competency Improvement (ECI) program to enhance students' English speaking skills at MA Bilingual Muslimat NU. Utilizing Classroom Action Research (CAR) with a descriptive phenomenological approach, data was collected through direct observation, interviews, and documentation. Results indicate that the ECI program effectively improves students' speaking skills, fostering enjoyment, discussion, and collaboration among students. The program involves two stages: preparation and process, allowing students to express opinions and ideas. Implications suggest that the ECI program positively contributes to enhancing students' speaking skills, advocating for the use of specific English-speaking teaching methods and encouraging active student participation.